Designing for positive user experience in work contexts: Experience categories and their applications - Zeiner, Katharina; Burmester, Michael; Haasler, Kristin; Henschel, Julian; Laib, Magdalena; Schippert, Katharina (Human Technology, 2018)
Experience categories describe repeatedly occurring qualities of positive experiences that can be used for the analysis and generation of new/further/more positive experiences. This paper describes experience categories for the workplace. Based on 345 reports of positive user experiences in the workplace, we identified 17 experience categories through qualitative content analysis and describe their necessary and optional attributes. We believe that experience categories can support analysis and design activities for the work place in three ways: (a) using the questions derived from experience interviews to analyze existing positive experiences in work contexts, (b) explaining the potential of positive experiences in work contexts as a formal analysis tool, and (c) showing the ways in which experience categories can inform the design of software concepts to foster/generate positive user experience. The experience category approach is thus a more actionable addition to other, mainly theory-driven, approaches.